Raising Awareness of Gender-Based Violence on Heaven Earth - Rahayu, Nila Sukmaning (European Journal of Sustainable Development, 2016)
This study criticizes the attitude of Indonesian government and provides policy recommendations to tackle the structural problem lied under the violence against women. The methods that are in the form of normative research approach conceptually, with the study of documents as well as secondary legal literatures. The rate of violence against women keeps increasing each year. It assesses Indonesia to be a state of sexual violence emergency. Meanwhile, the Indonesian government seeks to aggravate the punishment for perpetrators to increase the maximum period of imprisonment for 20 years and provide additional punishment in the form of chemical castration, chip mounting, and the publication of the identity of the perpetrators. On the other hand, The National Commission on Violence Against Women’s demand to strengthen Indonesian law implementation first before others. This research is about to seek what best resolution could be obtained from the dispute while analyzing the case from the view of feminism. Keywords: Gender, Government, Policy, Punishment, Sexual, Violence.